Systemic Therapy Combined with Locoregional Therapy Improved Survival in Oligometastatic Breast Cancer: A Single-Center Retrospective Cohort Study. (20th September 2022) - Ma, Yuyu; Duan, Fangfang; Zhuang, Yue; Song, Chenge; Huang, Jiajia; Xia, Wen; Hong, Ruoxi; Zheng, Qiufan; Wang, Shusen; Shi, Yanxia; Xu, Fei; Yuan, Zhongyu; et al.
Abstract : The optimal therapeutic options, adding locoregional therapy (LRT) to systemic therapy (ST) or not, for patients with oligometastatic breast cancer (OMBC) have not been fully elucidated. Hence, we designed a retrospective observational study which enrolled patients with measurable extracranial OMBC having less than 5 metastatic lesions not necessarily in the same organ. We retrospectively reviewed a total of 199 patients diagnosed with extracranial OMBC, including 28 receiving ST followed by LRT (ST to LRT group), 44 receiving LRT followed by ST (LRT to ST group), and 127 receiving ST alone (ST alone group). After a median follow-up of 28.7 months, patients receiving both ST and LRT had a significantly better prognosis than those receiving ST alone: the median progression-free survival (PFS) was 16.3, 14.0, and 9.3 months (P < 0.001 ) and the median overall survival (OS) was 39.8, 70.5, and 26.7 months (P < 0.001 ) in the ST to LRT, LRT to ST, and ST alone groups, respectively. Sequence of ST and LRT had no significant impact on survival among patients receiving both. Further exploratory analysis identified ST plus LRT as an independent predictor for longer PFS. In conclusion, we demonstrated that adding LRT to ST was associated with survival benefits for patients with OMBC, and further prospective studies were warranted.